RIO DE JANEIRO - Schøllhammer, Karl Erik (Tidsskriftet Antropologi, 2003)
The essay discusses the visual characteristics of Rio de Janeiro trying to understand the identification of the “cariocas” with their city as attached to the monumental staging of urban visuality in the privileged relation between city and nature. In the frame of the macro-historical construction of Rio de Janeiro as an emblem of the Brazilian nation and as the international representative postcard of Brazil, the essay points out another micro-relation between the inhabitants’ possibility of a visual dominion of the urban complexity and the special process of sensual identification with the city, that has characterised Rio as the cultural capital.